PP.LB03.27: NEED FOR INFORMATION AND LOCUS OF CONTROL AMONG HYPERTENSIVE PATIENTS. (June 2015) - Vaccarella, A.; Steca, P.; Cappelletti, E.; D'Addario, M.; Greco, A.; Monzani, D.; Pancani, L.; Destro, M.; Cuspidi, C.
Abstract : Objective: Hypertension is a major health problem leading to high rates of mortality, morbidity and impaired quality of life. Due to high costs of hypertension and low adherence to treatment and lifestyles changes, the tasks of developing maximally beneficial treatment programs for individuals with this health problem have received growing emphasis in recent years. Patients with hypertension need appropriate information in order to take meaningful choices about their future, but information should be focused on patient's peculiar needs to be really effective. Research has highlighted the importance of the identification of information needs and their psychological correlates, in order to create tailored health communication interventions aimed at enhancing the effectiveness of the information provided. A promising construct in this field is Locus of Control (LOC), that refers to the extent to which individuals believe they can control and have power over events affecting their life. In the health context, LOC describes the belief that one's health is dependent upon internal (e.g. behavior) versus external factors (e.g. chance). This study was designed to investigate possible relationships between need for information and health LOC in patients with essential hypertension. Design and method: One hundred seventy-five patients (48.8% women; mean age = 63.68, SD = 10.90, range 26–86) completed an assessment questionnaire evaluating Multidimensional Health Locus of Control (MHLC) and the need for further information on topics related to disease management. Correlation analysis were conducted to explore the relationship between variables. Results: Positive and significant correlations were found between "Internal", "Doctors", "Other People" locus of control and need for information, while negative, but not significant, relationships were found between need for information and "Chance" locus of control. Conclusions: Taking into account patients' types of locus of control could enhance the quality of health communication interventions, leading health-care system to move toward a patient-tailored care.